Terminologia Histologica 10 years on: some disputable terms in need of discussion and recent developments - Varga, Ivan; Gálfiová, Paulína; Blanková, Alžbeta; Konarik, Marek; Báča, Václav; Dvořákova, Vlasta; Musil, Vladimír; Turyna, Radovan; Klein, Martin (Annals of anatomy, 2019)
At first sight, the issue of morphological terminology may seem to be a "closed and unchanging chapter", as many of the structures within the human body have been known for decades or even centuries. However, the exact opposite is true. The initial knowledge of the microscopic structure of the human body has been continuously broadening thanks to the development of new specialized staining techniques, discovery of the electron microscope, or later application of histochemical and immunohistochemical methods into routine tissue examination. Contrary to popular belief, histology has a status of constantly developing scientific discipline, with continuous influx of new knowledge, resulting in an unavoidable necessity to revise the histological nomenclature at regular intervals. The team of experts of the Federative International Programme on Anatomical Terminology, a working group of the International Federation of Associations of Anatomists, published in 2008 the First Edition of Terminologia Histologica. Terminologia Histologica (TH) is the best and most extensive of all the histological nomenclatures ever issued. However, here we suggest that several terms of important histological structures are still missing while several other terms are disputable. First, we present some clinically important terms of cells and tissue structures for inclusion in the next TH and, in a second part, we refer to some new terms in the current edition of the TH which are not yet mentioned in current histology textbooks (e.g., fusocellular connective tissue, bundle bone as the third type of bone tissue, spongy layer of vagina or arteria vaginata from the splenic white pulp). With this article we hope to start a wide scientific discussion which will lead to an inambiguous definition and demonstration of typical examples of all terms in the TH, with the result that the new edition of the Terminologia Histologica will become an internationally accepted communication tool for all practitioners and teachers of histology alike.
Keywords: terminologie jako téma; histologie; anatomové; Reference Books, Medical; Histology; Terminology as Topic; lidé; Histological terminology; příručky lékařské; Cells; anatomie; buňky; Histological nomenclature; Anatomy; Terminologia Histologica; Anatomists; Humans